Advancing Hospital Service Quality and Operational Effectiveness through Evidence-Based Analgesic Protocols: JEL Classification: I11, I12, I18, L15, M11, D24 - Hermawan, Andi; Romadhon, Yusuf Alam; Imronudin, Imronudin (Newinera Publisher, 2025)
The study is aimed at comparing the clinical and institutional outcomes of using two postoperative analgesics regimens, Epidural Levobupivacaine and Syringe Pump Fentanyl, and how these drugs interfere with analgesia control and resource consumptions, patient satisfactory, and system performance. A comparative observational research design was used which covered 60 patients of Total Knee Replacement (TKR) who were in a tertiary orthopedic center. The participants were at random allocated to an Epidural Levobupivacaine or Fentanyl protocol. The collected data included pain scores, adverse events, the readiness of the patient to leave, and satisfaction questionnaires and efficiencies of hospitals in terms of data. The data were analyzed using descriptive and comparative approaches. The Epidural group of patients recorded less pain scores, fewer adverse effects, earlier mobilization and shorter length of stay. The scores of the satisfaction on pain control, comfort and responsiveness were significantly more in the Epidural group. The mode of operation also demonstrated better nursing efficiency and discharge planning, and risk indicators were reduced, e.g. escalation to high-dependency care, with the use of the epidural protocol. Epidural Levobupivacaine represents an effective operational and clinical performance that demonstrates that it can be used as a strategical standar in elective orthopedis care based on systemic opioids. In addition to the analgesic effectiveness, the protocol improves institutional efficiency, minimizes the clinical risk, intensifies patient experience and fits the contemporary performance-based healthcare provision. Pain management must therefore be redefined as an impact component that has a cross-functional component of hospital service design.